THE PSYCHIATRIC REFORM IN THE SAÚDE EM DEBATE MAGAZINE REPORTS THROUGH 1985 - 1995 - Vera Lúcia Miron; Luciane Prado Kantorski; Ana Celeste de Araújo Pitiá (Universidade Federal de Goias, 2002)
In this paper we make a study of related articles about the Brazilian psychiatric reform published inthe Saúde em Debate Magazine from february/1985 to june/1995. 17 texts were examined in two blocks: 1989-1991 and 1992-1994, according to their main axis: assistance model, citizenship and paw. It was observed that thistheme is relatively recent in the magazine, in consonance with the history of the psychiatric reform process. Theheterogeneity of the reform proposes, that is comprehensible due the Brazilian regional diversity and severalinterests at take, express it in the publications. The analyzed texts make theoretical reflections from concreteexperiences guided to the reform process.